PERAN GENDER DEWAN DIREKSI SEBAGAI PEMODERASI CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN - Maria Apriliuni Yeni Mali; Aminul Amin (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
This study was conducted with the aim of testing and analyzing the effect of corporate social responsibility, financial performance with the gender of the board of directors as a moderating variable. This study uses a quantitative research type, the research sample used is a mining company listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period as many as 12 companies. The analytical method used is Moderated Regression Analysis (MRA) using the Statistical Package for the Social Sciences (SPSS). The results obtained from this study are that corporate social responsibility has a significant effect on interest in use, board gender has a significant effect on financial performance. Based on the results of the Moderated Regression Analysis (MRA) test, the gender of the board does not moderate the effect of corporate social responsibility and financial performance.